Multifactorial Dermatitis in an Elderly Patient with Chronic Actinic Dermatitis: A Case Report - Sunardi, Hendry Purnomo; Sutedja, Gina Triana (Medicinus, 2025)
Background : Chronic actinic dermatitis (CAD) is a rare, persistent photodermatosis triggered by UV and visible light, primarily affecting elderly individuals. With multifactorial etiologies, including genetic predisposition, environmental exposure, and comorbidities, CAD significantly impacts quality of life. This case report presents an elderly farmer with CAD, emphasizing the complexities of diagnosis and management in individuals exposed to high levels of sunlight due to occupational factors. Methods : A 70-year-old male farmer presented with a two-week history of pruritus and burning sensations on his face, exacerbated by sun exposure. He had a history of seborrheic dermatitis and hypertension. Physical examination revealed erythematous, hyperpigmented plaques on sun-exposed areas, with macular erythema, erosion, and lichenification. The working diagnosis was CAD, with actinic prurigo and cutaneous T-cell lymphoma as differentials. Management included methylprednisolone, cetirizine, and a compounded cream containing clobetasol propionate and gentamicin. Preventive measures, such as the use of moisturizers, sunblock, and UV avoidance, were also emphasized. The prognosis was favorable for life and function but uncertain for complete remission due to CAD's chronic nature. Conclusions : This case underscores the importance of an integrated approach combining pharmacological treatment and preventive strategies to manage CAD effectively. Tailored interventions addressing occupational and environmental risk factors are vital. Diagnostic limitations highlight the necessity for follow-up and the development of enhanced diagnostic tools. CAD management requires multidisciplinary collaboration to optimize patient outcomes.